Secured bicycle parking rack for UiTM Pasir Gudang / Nurul Nurfaizzah Abdullah - Abdullah, Nurul Nurfaizzah (2022)
This project is about designing and fabricating bicycle parking rack for UiTM Pasir Gudang. There are a few problems when the students bring their bicycle to the campus. There is no specific parking for the bicycles and so many cases of bicycle theft reported in a year because of the lacking of security for bicycle. In order to overcome these problems, this project will be designing a parking rack that can ease the bikers. In addition, the project also will fabricating a parking rack that secured with locking system in order to prevent bicycle theft